Fault monitoring system for traffic light - Marzuki, Muhamad Zaki Amin (Penerbit UTM Press, 2015)
Traffic light breakdown is very common. These create hassle as well as unsafe condition for road users. This project provides a new paradigm in traffic light monitoring system. The system has the capability to send multiple Short Message Service (SMS) to the contractor, traffic police and local council in the event of a malfunction traffic light. Normally, road users have to call the contractor based on the information displayed at the traffic light pole. With the current system, time taken to respond to the traffic light breakdown depends on how soon road users call the contractor. Monitoring system for fault traffic light will address this matter. In this project, the system can detect two types of failure, power failure and bulb/ Light Emitting Diode (LED) failure (a particular light not working i.e. red light only). Upon receiving the power failure signal, SMS will be sent to the above-mentioned parties for further action. For LED types of traffic light, the system has the capability to detect deterioration in function. If >50% of the LED for any light is not working the system will notify the contractor and other related parties to perform restorative action. The malfunction of LED can be detected by measuring real current vs the nominal current for that particular light. The seriousness of traffic light failure is divided into three parts, which are the total power failure, total LED failure and partial failure. The microcontroller analyzes the seriousness of the failure and sends the signal to a Global System for Mobile communications (GSM) module. Then the GSM module will send the details of failure including location and types of failure. For this project, LED was used as prototype of the traffic light